Ticks associated with wild animals in the Nhecolândia Pantanal, Brazil - Bechara, G. H. [UNESP]; Szabó, M. P J [UNESP]; Duarte, J. M B [UNESP]; Matushima, E. R. [UNESP]; Campos Pereira, M. [UNESP]; Rechav, Y. [UNESP]; Keirans, J. E. [UNESP]; Fielden, L. J. [UNESP] (Wiley, 2000)
A study of ticks associated with wild animals was carried out from September 1996 to April 1998 at the Fazenda Alegria (21,000 ha), in the Nhecolândia Pantanal, State of Mato Grosso do Sul, Brazil, a sunken plain bordering the upper Paraguay river, located 19 × 08′S; 56 × 46′W. A total of 81 wild animals (13 species, 6 orders) were captured with the aid of nets, and ticks were found on 63 (78%). Tick species identified included Boophilus microplus (Canestrini), Amblyomma cajennense (F.), A. parvum (Aragão), A. pseudo-concolor (Aragão), A. scalpturatum (Neumann), A. nodosum (Neumann), A. ovale (Koch), and A. tigrinum (Koch). Dragging from grasslands (campos) yielded negative results compared to the high concentration of ticks, mainly nymphs, that were collected from leaves in the forests (capão). Predominance of immature instars (Amblyomma genera) was observed in the end of winter (August-September). Ticks were associated mainly with coatis, deer (Mazama gouazoubira) and anteater, and these animals may play a role in the epidemiology of tick-transmitted pathogens in the Pantanal if one considers their coexistence with local domestic animals.
Keywords: animal disease; anteater; Brazil; conference paper; deer; disease transmission; infestation; nonhuman; parasite identification; tick; wildlife; Animals; Animals, Wild; Geography; Ixodes; Poaceae; Tick Infestations; Ticks; Trees; Tropical Climate; Acari; Amblyomma cajennense; Amblyomma nodosum; Amblyomma ovale; Amblyomma tigrinum; Animalia; Arachnida; Boophilus microplus; Caesalpinia ciliata; Cervidae; Hexapoda; Mazama; Mazama gouazoubira; Myrmecophagidae; Nasua